High Electric Field Carrier Transport and Power Dissipation in Multilayer Black Phosphorus Field Effect Transistor with Dielectric Engineering. (14th December 2016) - Ahmed, Faisal; Kim, Young Duck; Choi, Min Sup; Liu, Xiaochi; Qu, Deshun; Yang, Zheng; Hu, Jiayang; Herman, Irving P.; Hone, James; Yoo, Won Jong
Abstract : This study addresses high electric field transport in multilayer black phosphorus (BP) field effect transistors with self‐heating and thermal spreading by dielectric engineering. Interestingly, a multilayer BP device on a SiO2 substrate exhibits a maximum current density of 3.3 × 10 10 A m −2 at an electric field of 5.58 MV m −1, several times higher than multilayer MoS2 . The breakdown thermometry analysis reveals that self‐heating is impeded along the BP–dielectric interface, resulting in a thermal plateau inside the channel and eventual Joule breakdown. Using a size‐dependent electro‐thermal transport model, an interfacial thermal conductance of 1–10 MW m −2 K −1 is extracted for the BP–dielectric interfaces. By using hexagonal boron nitride (hBN) as a dielectric material for BP instead of thermally resistive SiO2 (κ ≈ 1.4 W m −1 K −1 ), a threefold increase in breakdown power density and a relatively higher electric field endurance is obtained together with efficient and homogenous thermal spreading because hBN has superior structural and thermal compatibility with BP. The authors further confirm the results based on micro‐Raman spectroscopy and atomic force microscopy, and observe that BP devices on hBN exhibit centrally localized hotspots with a breakdown temperature of 600 K, while the BP devices on SiO2 exhibit hotspots in the vicinity of the electrode at 520 K. Abstract : An electrical breakdown thermometry technique is employed to study the power dissipation in a multilayer black phosphorus field‐effect transistor. The dielectric–black phosphorus interface serves as thermal bottleneck; hence, an efficient thermal spreading is realized via dielectric engineering. This scheme will be beneficial to realize durable and energy‐efficient electronic circuits based on 2D materials.